Kejahatan Terorganisir Terhadap Pelacuran Anak Di Kota Medan Ditinjau Dari Psikologi Kriminil (Studi Penelitian di Kota Medan) - Lubis, Muhammad Ridwan (Jurnal Hukum Kaidah: Media Komunikasi dan Informasi Hukum dan Masyarakat, 2020)
Crimes that used to be committed by individuals are now mostly committed by organized groups where the legal force of the group is illegal. Theft, muggings, fraud, murder, corruption, money loundry, prostitution, terrorism are some forms of the crime that are mostly committed in an organized manner.The development of the world of the child prostitution has spread in various big cities in Indonesia, including Medan. The sparkling of the city has attracted many people who come from various places in Indonesia and outside Indonesia who want to taste the sweetness of the sparkle of the city with all its spices like a laron approaching a torch which eventually destroys them. The condition of the child prostitution in Medan City has become apprehensive where many children aged 14-17 are involved in the prostitution business. Their involvement tends to be due to the factor of deception committed by collectors who work as collectors and suppliers of children to the prostitution places. This crime was committed in an organized manner as evidenced by the existence of syndicates that collaborated, ranging from child collectors and suppliers (collectors) and those who accommodate and employ children as the prostitutes (pimps / pimps), with recruitment areas covering malls, plazas, suburban areas, as well as other entertainment centers, which are generally the place where teenagers hang out.In conclusion, the factors that cause organized crime against the child prostitution in Medan are environmental factors (there is good interaction and communication between them, both those from the same environment and those from different environments), economic factors and unemployment and which is very dominant is the psychological factor. The obstacles that are faced in overcoming organized crime against the child prostitution business are the obstacles in terms of legislation due to weaknesses rather than the scope of the law itself in ensnaring perpetrators of criminal acts of the child prostitution as well as the criminal threats which are still classified mild.Keywords : Organized Crime, Child Prostitution, Criminal Psychology